2010
DOI: 10.7322/jhgd.19976
|View full text |Cite
|
Sign up to set email alerts
|

A Comparação de funções apendiculares desencadeadas pela visão em lactentes nascidos pré-termo e a termo no primeiro trimestre de vida

Abstract: OBJETIVO: caracterizar e comparar o desenvolvimento de funções apendiculares entre dois grupos de lactentes a termo e pré-termo e verificar se a fixação visual pode ser considerada como um pré-requisito para as ações dos membros superiores. MÉTODO: estudo realizado no Centro de Estudos e Pesquisas em Reabilitação"Prof. Dr. Gabriel Porto", da Universidade Estadual de Campinas em dois grupos: 1) pré-termo, constituído de 21 lactentes, com idade corrigida entre 1 e 3 meses e 2) 21 recém-nascido a termo. Para aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
(48 reference statements)
0
3
0
10
Order By: Relevance
“…15,12,18 In preterm infants (± 27 weeks gestational age) at high-risk of delays in neuromotor development and brain disorders, it was found that the acquisition of reaching occurred later, with the hand completing the trajectory more slowly, and in addition, with less fluent movements of the upper limbs than full-term infants. 17,19 Such differences may be explained by deficits in postural control, in the control of axial motricity, in the development of oculomotor functions, in eye-hand and visual-motor coordination, low muscle tone and hyperextension of the trunk by these infants. 19,8 Considering that prematurity has been linked to limitations in the behavior of manual reaching in the first months of life, it is very relevant to provide sensorimotor experiences in order to promote the improvement of reaching in infants, since the practice of a skill can lead to an improvement in its performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,12,18 In preterm infants (± 27 weeks gestational age) at high-risk of delays in neuromotor development and brain disorders, it was found that the acquisition of reaching occurred later, with the hand completing the trajectory more slowly, and in addition, with less fluent movements of the upper limbs than full-term infants. 17,19 Such differences may be explained by deficits in postural control, in the control of axial motricity, in the development of oculomotor functions, in eye-hand and visual-motor coordination, low muscle tone and hyperextension of the trunk by these infants. 19,8 Considering that prematurity has been linked to limitations in the behavior of manual reaching in the first months of life, it is very relevant to provide sensorimotor experiences in order to promote the improvement of reaching in infants, since the practice of a skill can lead to an improvement in its performance.…”
Section: Introductionmentioning
confidence: 99%
“…17,19 Such differences may be explained by deficits in postural control, in the control of axial motricity, in the development of oculomotor functions, in eye-hand and visual-motor coordination, low muscle tone and hyperextension of the trunk by these infants. 19,8 Considering that prematurity has been linked to limitations in the behavior of manual reaching in the first months of life, it is very relevant to provide sensorimotor experiences in order to promote the improvement of reaching in infants, since the practice of a skill can lead to an improvement in its performance. 11,[20][21][22][23][24][25] In preterm infants of less than 33 weeks gestational age, it was found that 4-6 weeks of reaching training through object-oriented movements favored longer contact of the hand with the toy, and after 8 weeks of training showed more reaching with open hand and with the ventral surface of the hand than the untrained preterm infants, becoming quite similar to the reaching of full-term infants.…”
Section: Introductionmentioning
confidence: 99%
“…15 Another important factor relating to premature vision refers to the fact that the pupillary response of the NB is established between 30-34 weeks of gestation. However, if preservation of the light does not occur continuously focus on the retina of newborns can result in losses in visual acuity.…”
Section: Resultsmentioning
confidence: 99%
“…No Brasil, a incidência de prematuridade entre os nascimentos tem variado de 5 a 15% e nos recém-nascidos pré-termo (RNTP) que sobrevivem, 1,3 tem levado à maior incidência de distúrbios neurosensorimotores, quando comparados a bebês a termo, em decorrência da imaturidade funcional e estrutural nos sistemas 4,5,6,7,8 .…”
Section: Introductionunclassified
“…As crianças prematuras, no que concerne ao desenvolvimento visual, estão mais propensas a desenvolver alterações oftalmológicas como a retinopatia da prematuridade, o estrabismo e os erros de refração resultantes das lesões neurológicas, da toxidade pela luz e da privação sensorial no período de intenso desenvolvimento do sistema visual compreendi-do entre 28-40 semanas 5,6,7 e com relação ao desenvolvimento motor, os prematuros, normalmente apresentam a alterações do tono muscular, reflexos primitivos ausentes ou diminuídos e movimentos espontâneos reduzidos, podendo apresentar atrasos na aquisição de controle da motricidade axial, apendicular e visuomotora 3,9 .…”
Section: Introductionunclassified